2003
DOI: 10.1177/0748730403251732
|View full text |Cite
|
Sign up to set email alerts
|

Is Sleep per se a Zeitgeber in Humans?

Abstract: It is not clear whether shifting of sleep per se, without a concomitant change in the light-dark cycle, can induce a phase shift of the human circadian pacemaker. Two 9-day protocols (crossover, counterbalanced order) were completed by 4 men and 6 women (20-34 years) after adherence to a 2330 to 0800 h sleep episode at home for 2 weeks. Following a modified baseline constant routine (CR) protocol on day 2, they remained under continuous near-darkness (< 0.2 lux, including sleep) for 6 days. Four isocaloric mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 24 publications
4
53
1
2
Order By: Relevance
“…The direction and magnitude of DLMO and CBT minimum phase shifts also were positively related, demonstrating a direct effect on the circadian timing system, similar to other studies (8,18,20,23,30,39,58). DLMO occurred a little over 7 h before CBT minimum, at baseline and after exposure, with a positive relationship between the two markers, as has been reported previously (7,9,14,23).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The direction and magnitude of DLMO and CBT minimum phase shifts also were positively related, demonstrating a direct effect on the circadian timing system, similar to other studies (8,18,20,23,30,39,58). DLMO occurred a little over 7 h before CBT minimum, at baseline and after exposure, with a positive relationship between the two markers, as has been reported previously (7,9,14,23).…”
Section: Discussionsupporting
confidence: 71%
“…Notably, one study failed to detect dilation at decibel levels comparable with that used in this study (53). To investigate this question further, subsequent studies could examine the effects of musically enhanced bird song in subjects maintained under conditions of near darkness (6,20) or in the totally blind (42), as has been done for other nonphotic stimuli, or could test subjects in the paradigm used by Cajochen et al (16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the magnitude of the effect of non-photic stimuli observed in Model PNP predictions is small enough that it could be (a) masked by the stronger effects of light in that and other studies, (b) lost in the variability of circadian phase markers due to sensitivity of the assays, or (c) confounded by the natural drift in the pacemaker as well as background light levels. Other studies have reported that timing of sleep (Danilenko et al, 2003) may have an effect on the circadian pacemaker, independent of light. Furthermore, our theoretical non-photic PRC generated by Model PNP has a similar shape as compared to other non-photic PRCs observed in humans in response to exercise and exogenous melatonin, findings which indicate that there is a 12-h anti-phase relationship to the light PRC.…”
Section: Discussionmentioning
confidence: 99%
“…One study of a forced 24-h sleep-wake schedule in dim light (~5 lux) suggests that the imposed rest-activity cycle may be sufficient to entrain the pacemaker of some subjects to the 24-h day (Nakamura, 1996). In a more recent experiment, subjects scheduled to a protocol that advanced the sleep-wake schedule by less than one hour each day (T = ~23.67 h) in <0.2 lux phase advanced towards the entraining stimuli compared to control subjects in the same lighting condition scheduled to a T = 24.0-h protocol (Danilenko et al, 2003). In studies that examined the effect of sleep deprivation on the circadian pacemaker, it has been reported that a 40-h sleep deprivation in dim light (between ~1.5 and 13 lux) induced, on average, a phase delay shift Wright et al 2005) that was larger than that which could be explained by the drift due to intrinsic period of the circadian pacemaker .…”
Section: The Effects Of Non-photic Stimuli On the Mammalian Circadianmentioning
confidence: 99%
“…Even a minimal misalignment between circadian phase and sleep phase can deteriorate mood (Danilenko et al 2003), which may also in part explain mood-related problems (e.g., irritability) in jet-lag (Waterhouse et al 2005), and severity of unipolar depression (Hasler et al 2010). Stress can also disrupt the circadian cycle (Meerlo et al 2002), leading to depressive episodes in vulnerable individuals (Ehlers et al 1988).…”
Section: Sleep Disturbance Causes Waking Emotional Dysfunctionsmentioning
confidence: 99%